Multibody mechatronic systems Papers from the MuSMe Conference in 2020 - Pucheta, Martín; Cardona, Alberto; Preidikman, Sergio; Hecker, Rogelio (Springer, 2021)
This book gathers the latest advances, innovations, and applications in the field of multibody and mechatronic systems. Topics addressed include the analysis and synthesis of mechanisms; dynamics of multibody systems; design algorithms for mechatronic systems; robots and micromachines; experimental validations; theory of mechatronic simulation; mechatronic systems for rehabilitation and assistive technologies; mechatronic systems for energy harvesting; virtual reality integration in multibody and mechatronic systems; multibody design in robotic systems; and control of mechatronic systems. The contents reflect the outcomes of the 7th International Symposium on Multibody Systems and Mechatronics (7th MuSMe) in 2020, within the framework of the FEIbIM Commission for Robotics and Mechanisms and IFToMM Technical Committees for Multibody Dynamics and for Robotics and Mechatronics.